Investigating the growth characteristics, oxidative stress, and metal absorption of chickpea (Cicer arietinum L.) under cadmium stress and in silico features of HMAs proteins - Maryam KOLAHI; Elham Mohajel KAZEMI; Milad YAZDI; Mina KAZEMIAN; Andre GOLDSON-BARNABY (Acta Agriculturae Slovenica)
Heavy metal contamination can have a strong effect on the morphological and physiological characteristics of plants. In the present study, Cicer arietinum L. (chickpea) was exposed to different concentrations of cadmium (control, 2, 4, 8 μg Cd g-1 perlite) and the effect on plant growth and antioxidant enzymes were evaluated. The observed morphological changes in chickpea plant included stunted growth, reduced root system development and plant color change. A significant increase in enzyme activity of peroxidase, superoxide dismutase, catalase, and ascorbate peroxidase was observed at 4 μg Cd g-1 perlite, with a subsequent decrease when concentration was increased to 8 μg Cd g-1 perlite in the leaves of the plants. The highest cadmium levels were determined at a concentration of 8 μg Cd g-1 perlite. With the addition of 2 μg Cd g-1 perlite, manganese uptake in the aboveground part of the plant increased significantly, but then decrease at higher cadmium concentrations. In addition, zinc and copper levels decrease in the presence of cadmium. These results indicate that chickpea has a relatively high adsorption capacity for cadmium in aboveground tissues and special precautions should be taken when growing chickpea. In silico analysis led to the identification of 13 heavy metal ATPases (HMAs) in chickpea. These proteins contain 130 to 1032 amino acids with 3 to 18 exons. They are involved in the transfer of cadmium and zinc and help in heavy metal detoxification of plants. Bioinformatics studies have been conducted to better understand the mechanism by which the plant is able to combat heavy metal stress.